Comparative amelioration of renal histomorphology by ascorbic acid and Camellia sinensis extract in Wistar rats exposed to Lead-induced nephropathy - Rotimi Omotoso, Dayo; Mathew Owonikoko, Wasiu; Prince Ehiemere, Winners (Annals of Medical Research, 2021)
Aim: To compare the ameliorative effects of ascorbic acid and Camellia sinensis extract on renal histomorphology of lead-induced nephropathic rats. Material and methods: Twenty four rats were randomly grouped into four groups (I–IV) as follows: Normal control group I administered distilled water (5 ml/kg), Test control group II administered lead acetate (2 mg/ml), Treated group III administered lead acetate (2 mg/ml) + ascorbic acid (100 mg/kg), Treated group IV administered lead acetate (2 mg/ml) + Camellia sinensis extract (10 mg/kg). All administrations were done through oral route and lasted for 30 days. Results: Body and renal tissue weight of study animals were significantly reduced (p 0.05) in test control relative to normal control while treated groups showed non-significant reduction. Histological examination of renal tissue showed significant prominence of histopathological features such as inflammation, necrosis and glomerular congestion in test control group while treated groups showed marked reduction.Conclusion: According to the findings of this study, treatment with ascorbic acid or Camellia sinensis extract comparatively exert ameliorative effects on lead-induced nephropathy in Wistar rats which in turn culminates into reparative influence on their renal histomorphology.